Wear-resistant high-elasticity foam and preparation method thereof
By adding wear-resistant modified components and inorganic modified fillers to IXPE foam, the wear-resistant and flame-retardant properties of foam are improved, and the problem of easy damage to existing IXPE foams under friction and high temperature is solved, achieving the goal of achieving It has a higher service life and market competitiveness.
Patent Information
- Application Number
- CN202411749917.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-07
AI Technical Summary
The existing IXPE foam is prone to surface damage, deformation, and fracture under friction or external force, and its flame retardant performance is poor, poses safety hazards, and is difficult to meet the diversified and high-value-added market demand.
Low-density polyethylene is used as the main raw material, and the foam matrix material is filled and modified by adding wear-resistant modification components and inorganic modification fillers. The preparation method includes steps such as mechanical stirring, extrusion, irradiation crosslinking and foaming to form foam with high elasticity, good wear resistance and flame retardant properties.
It significantly improves the wear resistance and flame retardant properties of foam, extends the service life, improves market competitiveness, and ensures the wear resistance and stability of foam during long-term use.
Smart Images

Figure CN119391037A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam, and in particular to a wear-resistant and highly elastic foam and a preparation method thereof. Background Art
[0002] Foam is a material made by foaming plastic particles, referred to as foam. It is popular because of its advantages such as light weight, environmental protection, thermal insulation and good processing performance. Foam mainly includes polyurethane foam, IXPE foam and EVA foam. Among them, IXPE foam is made of polyethylene as the main raw material, and is prepared by adding auxiliary materials such as foaming agent and lubricant, through extrusion molding, radiation cross-linking and high-temperature foaming. It has the characteristics of dense pores, non-toxic and harmless, aging resistance, oil resistance, high elasticity and environmental protection. It is widely used in many fields such as construction, automobile, packaging, sports and leisure, medical equipment, etc.
[0003] With the development of science and technology and the progress of society, ordinary IXPE foam can no longer meet the diversified and high value-added market demand. Therefore, the functional development of IXPE foam has become an important trend in the development of the industry. IXPE foam may face wear problems in actual applications, and foam with poor wear resistance may suffer surface damage, deformation, fracture and other problems when subjected to friction or external force, which will not only reduce the service life of the foam, but also affect its overall performance. In addition, IXPE foam has poor flame retardant properties. When exposed to high temperature or open flame, it is easy to be ignited and cause fire, which poses a great safety hazard and greatly affects the application scope of IXPE foam. Therefore, IXPE foam still has certain shortcomings in practical applications.
[0004] In the prior art, in order to improve the performance of foam, functional additives are often used to fill and modify the foam. For example, the invention patent with announcement number CN102174223B discloses a flame-retardant foamed polyethylene material and a preparation method thereof. The invention adds an intumescent flame retardant and expanded vermiculite to a polyethylene matrix, so that the prepared material has good flame retardant properties. The intumescent flame retardant is compounded by trihydroxyethyl isocyanurate and ammonium polyphosphate in a mass ratio of 1:3, and cooperates with the flame retardant synergist expanded vermiculite to retard flame. However, the added expanded vermiculite is not organically modified, and its dispersibility in the matrix is not strong, and it is easy to agglomerate. Based on this, it is of great significance for the present invention to develop a foam with good wear resistance and flame retardant properties. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a wear-resistant and highly elastic foam and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing wear-resistant and highly elastic foam, the foam comprising the following raw materials in parts by weight: 40-50 parts of low-density polyethylene, 5-10 parts of a compatibilizer, 5-7 parts of a wear-resistant modified component, 4-6 parts of an inorganic modified filler, 8-12 parts of a foaming agent, 1-2 parts of zinc oxide, 1-3 parts of a black masterbatch, 1-2 parts of an antioxidant 168, and 1-3 parts of polyethylene wax;
[0008] The preparation method comprises the following steps:
[0009] (1) adding low-density polyethylene, compatibilizer, wear-resistant modification component, inorganic modified filler, foaming agent, zinc oxide, black masterbatch, antioxidant 168, and polyethylene wax into a mixer, mechanically stirring evenly, adding into a single screw extruder for extrusion, setting the extrusion section working temperature to 100-140° C., the screw speed to 50-150 r / min, extruding a sheet with a thickness of 0.4-0.8 mm, and obtaining a master sheet;
[0010] (2) irradiating and crosslinking the master sheet obtained in step (1) using an electron accelerator to obtain an irradiated and crosslinked master sheet;
[0011] (3) Adding the radiation cross-linked mother sheet into a foaming furnace for foaming treatment, setting the temperature of the foaming furnace to 200-240° C. and the foaming time to 6-10 min to obtain foam.
[0012] Furthermore, the preparation method of the wear-resistant modified component comprises the following steps:
[0013] Ⅰ: Mix eucommia gum and petroleum ether, stir mechanically to dissolve, add formic acid, mix well, add hydrogen peroxide, stir for 1 to 2 hours at 40 to 50°C, discharge, wash and vacuum dry to obtain epoxidized eucommia gum;
[0014] Ⅱ: Add epoxidized eucommia gum and dimethyl sulfoxide solution into a nitrogen-protected reactor, stir evenly, then continue to add ferrocenecarboxylic acid and catalyst into the reactor, raise the system temperature to 70-90°C under stirring conditions, keep warm for 5-7 hours, wait for the material to cool naturally, discharge the material, and obtain a wear-resistant modified component.
[0015] Furthermore, in step I, the mass fraction of the hydrogen peroxide is 20% to 50%.
[0016] Furthermore, in step II, the catalyst is any one of benzyltriethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.
[0017] The principle of the above technical scheme is: in the wear-resistant modified component, first, the unsaturated double bonds in the structure of Eucommia ulmoides gum are epoxidized through an epoxidation reaction to form epoxy groups, thereby obtaining epoxidized Eucommia ulmoides gum; secondly, under the action of a catalyst, the epoxy groups in the epoxidized Eucommia ulmoides gum structure can undergo a ring-opening reaction with the carboxyl groups in ferrocenecarboxylic acid, thereby introducing active hydroxyl groups into the structure of Eucommia ulmoides gum to obtain a wear-resistant modified component.
[0018] Furthermore, the preparation method of the inorganic modified filler comprises the following steps:
[0019] Add glass flakes and xylene solution into a reaction kettle, perform ultrasound to form a uniform dispersion, pass nitrogen, expel the air, then add diisocyanate monomer and tin catalyst into the dispersion, after the addition is completed, turn on the heating until the temperature in the reaction kettle reaches 85-95°C, keep stirring for 3-5 hours, then add N, N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, lower the system temperature to 60-70°C, stir under this temperature condition for 3-7 hours, filter and separate the solid material, wash the solid material, and vacuum dry to obtain modified glass flakes.
[0020] Furthermore, the diisocyanate monomer is any one of toluene-2,4-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate or diphenylmethane-4,4'-diisocyanate.
[0021] Furthermore, the tin catalyst is any one of stannous octoate, dibutyltin didodecylsulfide or dibutyltin dilaurate.
[0022] The principle of the above technical solution is: in the inorganic modified filler, firstly, since the diisocyanate monomer contains two isocyanate groups with high reactivity, under the action of a tin catalyst, one of them can chemically react and bond with the silanol groups on the surface of the glass flakes, thereby introducing highly active isocyanate groups on the surface of the glass flakes to obtain modified glass flakes; secondly, the isocyanate groups on the surface of the modified glass flakes are used as active sites, which can further react with the hydroxyl groups in the structure of N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester to obtain an inorganic modified filler.
[0023] Furthermore, the foaming agent is any one of azodicarbonamide, p-toluenesulfonyl hydrazide or N,N-dinitrosopentamethylenetetramine.
[0024] Furthermore, in step (2), the radiation dose of the radiation cross-linking is 70 to 100 kGy.
[0025] A wear-resistant and highly elastic foam is made by adopting the above preparation method.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention uses low-density polyethylene as the main raw material to prepare IXPE foam, so that the prepared foam has high elasticity, and the foam base material is filled and modified by using a wear-resistant modified component and an inorganic modified filler. The raw materials cooperate with each other to effectively improve the wear resistance and flame retardant properties of the foam, extend the service life of the foam, and enhance the market competitiveness of the foam.
[0028] (2) The wear-resistant modified component prepared by the present invention is a eucommia gum derivative with a rigid structure. Since the wear-resistant modified component contains active hydroxyl groups, it can interact with the compatibilizer in the matrix during the mixing process, so that the wear-resistant modified component and the polyethylene molecular chain form an interpenetrating network structure, enhance the cohesion of the foam, increase the crosslinking density of the foam, and effectively improve the wear resistance of the foam. At the same time, the wear-resistant modified component can be stably present in the polyethylene molecules, ensuring the stability of the wear resistance of the foam during long-term use, thereby making the foam have a longer service life. Eucommia gum is a hard rubber with hard texture and wear resistance. Introducing it into polyethylene molecules can make the prepared foam have good wear resistance. In addition, ferrocene in the structure of the wear-resistant modified component is a rigid structure, which can effectively improve the hardness of the foam, which is beneficial to further improve the wear resistance of the foam and avoid surface damage, deformation, fracture and other problems of the foam when it is subjected to friction or external force.
[0029] (3) The inorganic modified filler prepared by the present invention is glass flakes with nitrogen-phosphorus flame retardant grafted on the surface. After being organically modified, the glass flakes have good interface properties with the polyethylene matrix and can be relatively evenly dispersed in the polyethylene matrix to form a good filling effect. On the one hand, since the glass flakes have a unique lamellar structure, they can form a stable physical barrier layer in the polyethylene matrix after being evenly dispersed, and produce a barrier effect to isolate the entry of heat and oxygen, protect the internal substrate from further combustion, and effectively improve the flame retardant properties of the foam. In addition, by adding glass flakes, the wear resistance of the foam can be further improved. On the other hand, the presence of nitrogen-phosphorus flame retardant in the inorganic modified filler can make the foam have good flame retardant properties, and can cooperate with the glass flakes to produce an organic-inorganic dual synergistic flame retardant effect, thereby achieving the goal of effectively improving the flame retardant properties of the foam with a relatively small addition amount, avoiding the negative impact of a large amount of inorganic modified filler on the performance of the foam.
[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0032] Figure 1 This is an infrared spectrum test chart of the wear-resistant modified component prepared in Example 1 of the present invention.
[0033] Figure 2 This is an infrared spectrum test chart of the inorganic modified filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] 1. Preparation of wear-resistant modified components
[0037] Ⅰ: 8g of eucommia gum and petroleum ether were mixed, mechanically stirred to dissolve, 1.6g of formic acid with a mass fraction of 88% was added, and after stirring evenly, 1.2g of hydrogen peroxide with a mass fraction of 30% was added at a rate of 2mL / min, and stirred at a temperature of 45°C for 1.5h, and the material was discharged, washed and vacuum dried to obtain epoxidized eucommia gum;
[0038] Ⅱ: Add 5g of epoxidized eucommia gum and dimethyl sulfoxide solution into a nitrogen-protected reactor, stir evenly, then continue to add 1g of ferrocenecarboxylic acid and 0.05g of tetrabutylammonium bromide into the reactor, raise the system temperature to 80°C under stirring conditions, keep warm for 6h, wait for the material to cool naturally, and discharge the material to obtain a wear-resistant modified component.
[0039] The wear-resistant modified components were analyzed by infrared spectroscopy using a Nicoleti S50 Fourier transform infrared spectrometer produced by Thermo Corporation of the United States. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of the wear-resistant modified component, 1759cm -1 The absorption peak of the ester group C=O appears at 3285cm -1 The absorption peak of hydroxyl group OH appears at 3095cm -1 The absorption peak of CH on the cyclopentadienyl ring appears at 1140 cm-1 The absorption peak that appears at is the characteristic absorption peak of monosubstituted ferrocenyl.
[0040] 2. Preparation of Inorganic Modified Fillers
[0041] Add 5g of glass flakes and xylene solution to the reactor, ultrasonicate to form a uniform dispersion, pass nitrogen, expel the air, then add 1.8g of isophorone diisocyanate and 0.05g of stannous octoate to the dispersion, turn on the heating until the temperature in the reactor reaches 90°C, keep stirring for 4h, then add 1.4g of N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, lower the system temperature to 65°C, stir at this temperature for 5h, filter and separate the solid material, wash the solid material, and vacuum dry to obtain modified glass flakes.
[0042] The infrared spectrum analysis of inorganic modified fillers was performed using Nicoleti S50 Fourier transform infrared spectrometer produced by Thermo Company of the United States. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of inorganic modified fillers, 1040cm -1 The absorption peak of Si-O appears at 3345 cm -1 The absorption peak of NH appears at 1405 cm -1 The absorption peak of CN appears at 1280cm -1 The absorption peak of P=O appears at 1060cm -1 The absorption peak of PO appears at
[0043] 3. Preparation of Foam
[0044] (1) 40 g of low-density polyethylene, 5 g of maleic anhydride grafted polyethylene, 5 g of wear-resistant modified component, 4 g of inorganic modified filler, 8 g of azodicarbonamide, 1 g of zinc oxide, 1 g of black masterbatch, 1 g of antioxidant 168, and 1 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 100° C., the screw speed was set to 50 r / min, and a sheet with a thickness of 0.4 mm was extruded to obtain a master sheet;
[0045] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 70 kGy to obtain a irradiated and crosslinked master sheet;
[0046] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 200° C. and the foaming time is 6 min to obtain foam.
[0047] Example 2
[0048] Preparation of foam
[0049] (1) 45 g of low-density polyethylene, 8 g of maleic anhydride grafted polyethylene, 6 g of wear-resistant modified component, 5 g of inorganic modified filler, 10 g of azodicarbonamide, 1.5 g of zinc oxide, 2 g of black masterbatch, 1.5 g of antioxidant 168, and 2 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 120° C., the screw speed was set to 100 r / min, and a sheet with a thickness of 0.6 mm was extruded to obtain a master sheet;
[0050] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 90 kGy to obtain a irradiated and crosslinked master sheet;
[0051] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 220° C. and the foaming time is 8 min to obtain foam.
[0052] The preparation method of the wear-resistant modified component and the inorganic modified filler is the same as that in Example 1.
[0053] Example 3
[0054] Preparation of foam
[0055] (1) 50 g of low-density polyethylene, 10 g of maleic anhydride grafted polyethylene, 7 g of wear-resistant modified component, 6 g of inorganic modified filler, 12 g of azodicarbonamide, 2 g of zinc oxide, 3 g of black masterbatch, 2 g of antioxidant 168, and 3 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 140° C., the screw speed was set to 150 r / min, and a sheet with a thickness of 0.8 mm was extruded to obtain a master sheet;
[0056] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at an irradiation dose of 100 kGy to obtain a irradiated and crosslinked master sheet;
[0057] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 240° C. and the foaming time is 10 min to obtain foam.
[0058] The preparation method of the wear-resistant modified component and the inorganic modified filler is the same as that in Example 1.
[0059] Comparative Example 1
[0060] Preparation of foam
[0061] (1) 45 g of low-density polyethylene, 8 g of maleic anhydride grafted polyethylene, 6 g of wear-resistant modified component, 10 g of azodicarbonamide, 1.5 g of zinc oxide, 2 g of black masterbatch, 1.5 g of antioxidant 168, and 2 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 120° C., the screw speed was set to 100 r / min, and a sheet with a thickness of 0.6 mm was extruded to obtain a master sheet;
[0062] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 90 kGy to obtain a irradiated and crosslinked master sheet;
[0063] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 220° C. and the foaming time is 8 min to obtain foam.
[0064] The preparation method of the wear-resistant modified component is the same as that in Example 1.
[0065] Comparative Example 2
[0066] Preparation of foam
[0067] (1) 45 g of low-density polyethylene, 8 g of maleic anhydride grafted polyethylene, 5 g of inorganic modified filler, 10 g of azodicarbonamide, 1.5 g of zinc oxide, 2 g of black masterbatch, 1.5 g of antioxidant 168, and 2 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 120° C., the screw speed was set to 100 r / min, and a sheet with a thickness of 0.6 mm was extruded to obtain a master sheet;
[0068] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 90 kGy to obtain a irradiated and crosslinked master sheet;
[0069] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 220° C. and the foaming time is 8 min to obtain foam.
[0070] The preparation method of the inorganic modified filler is the same as that in Example 1.
[0071] Comparative Example 3
[0072] Preparation of foam
[0073] (1) 45 g of low-density polyethylene, 8 g of maleic anhydride grafted polyethylene, 6 g of wear-resistant modified component, 4 g of glass flakes, 1 g of N, N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, 10 g of azodicarbonamide, 1.5 g of zinc oxide, 2 g of black masterbatch, 1.5 g of antioxidant 168, and 2 g of polyethylene wax are added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature is set to 120° C., the screw speed is set to 100 r / min, and a sheet with a thickness of 0.6 mm is extruded to obtain a master sheet;
[0074] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 90 kGy to obtain a irradiated and crosslinked master sheet;
[0075] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 220° C. and the foaming time is 8 min to obtain foam.
[0076] The preparation method of the wear-resistant modified component is the same as that in Example 1.
[0077] Comparative Example 4
[0078] Preparation of foam
[0079] (1) 45 g of low-density polyethylene, 8 g of maleic anhydride grafted polyethylene, 10 g of azodicarbonamide, 1.5 g of zinc oxide, 2 g of black masterbatch, 1.5 g of antioxidant 168, and 2 g of polyethylene wax were added to a mixer, mechanically stirred evenly, and then added to a single-screw extruder for extrusion, the extrusion section operating temperature was set to 120° C., the screw speed was set to 100 r / min, and a sheet with a thickness of 0.6 mm was extruded to obtain a master sheet;
[0080] (2) using an electron accelerator to irradiate and crosslink the master sheet obtained in step (1) at a irradiation dose of 90 kGy to obtain a irradiated and crosslinked master sheet;
[0081] (3) The irradiated cross-linked mother sheet is added into a foaming furnace for foaming treatment. The temperature of the foaming furnace is set to 220° C. and the foaming time is 8 min to obtain foam.
[0082] Performance testing:
[0083] The foams prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were made into samples that met the specifications. According to GB / T 3960-2016 "Test Method for Sliding Friction and Wear of Plastics", the friction and wear performance test was carried out on an M-2000 wear tester. The test load was 200N and the wear time was 2h. The wear resistance of the samples was evaluated by calculating the friction coefficient. According to GB / T 2411-2008 "Determination of Indentation Hardness (Shore Hardness) of Plastics and Ebonite Using a Durometer", the hardness test was carried out on the samples. According to GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test", the combustion performance test was carried out on the samples to evaluate the flame retardant performance of the samples. The specific test results are shown in Table 1:
[0084] Table 1 - Performance Test
[0085] Friction coefficient Shore Hardness Limiting oxygen index (%) Example 1 0.09 61 32.5 Example 2 0.08 63 32.8 Example 3 0.10 60 31.9 Comparative Example 1 0.18 53 23.3 Comparative Example 2 0.22 51 27.6 Comparative Example 3 0.14 56 25.7 Comparative Example 4 0.39 45 19.5
[0086] As shown in Table 1, the foams prepared in Examples 1 to 3 all have good wear resistance and flame retardancy, which is presumably because the added wear-resistant modified component and inorganic modified filler have good wear resistance and flame retardancy; the foam prepared in Comparative Example 1 does not add inorganic modified filler, and the flame retardancy of the sample is poor compared with the example; the foam prepared in Comparative Example 2 does not add wear-resistant modified component, and the wear resistance of the sample is not as good as that of the example, which is presumably because it can only rely on inorganic modified filler for wear resistance, resulting in a decrease in the wear resistance of the sample; the foam prepared in Comparative Example 3 does not add inorganic modified filler, and the wear resistance of the sample is poor compared with the example. Wear-resistant modification components, glass flakes and N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester were added to the foam. Compared with the examples, the wear resistance and flame retardancy of the samples were average. It is speculated that this may be because the added glass flakes were not highly dispersed in the matrix, agglomeration occurred, and N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester migrated in the matrix, resulting in a decrease in the wear resistance and flame retardancy of the samples. No wear-resistant modification components and inorganic modified fillers were added to the foam prepared in comparative example 4, so the performance of each sample was the worst.
[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing wear-resistant and highly elastic foam, characterized in that: The foam comprises the following raw materials in parts by weight: 40-50 parts of low-density polyethylene, 5-10 parts of compatibilizer, 5-7 parts of wear-resistant modification component, 4-6 parts of inorganic modified filler, 8-12 parts of foaming agent, 1-2 parts of zinc oxide, 1-3 parts of black masterbatch, 1-2 parts of antioxidant 168, and 1-3 parts of polyethylene wax; The preparation method comprises the following steps: (1) adding low-density polyethylene, compatibilizer, wear-resistant modification component, inorganic modified filler, foaming agent, zinc oxide, black masterbatch, antioxidant 168, and polyethylene wax into a mixer, mechanically stirring evenly, adding into a single screw extruder for extrusion, setting the extrusion section working temperature to 100-140° C., the screw speed to 50-150 r / min, extruding a sheet with a thickness of 0.4-0.8 mm, and obtaining a master sheet; (2) irradiating and crosslinking the master sheet obtained in step (1) using an electron accelerator to obtain an irradiated and crosslinked master sheet; (3) Adding the radiation cross-linked mother sheet into a foaming furnace for foaming treatment, setting the temperature of the foaming furnace to 200-240° C. and the foaming time to 6-10 min to obtain foam.
2. The method for preparing a wear-resistant and highly elastic foam according to claim 1, characterized in that: The preparation method of the wear-resistant modified component comprises the following steps: Ⅰ: Mix eucommia gum and petroleum ether, stir mechanically to dissolve, add formic acid, mix well, add hydrogen peroxide, stir for 1 to 2 hours at 40 to 50°C, discharge, wash and vacuum dry to obtain epoxidized eucommia gum; Ⅱ: Add epoxidized eucommia gum and dimethyl sulfoxide solution into a nitrogen-protected reactor, stir evenly, then continue to add ferrocenecarboxylic acid and catalyst into the reactor, raise the system temperature to 70-90°C under stirring conditions, keep warm for 5-7 hours, wait for the material to cool naturally, discharge the material, and obtain a wear-resistant modified component.
3. The method for preparing a wear-resistant and highly elastic foam according to claim 2, characterized in that: In step I, the mass fraction of the hydrogen peroxide is 20% to 50%.
4. The method for preparing a wear-resistant and highly elastic foam according to claim 2, characterized in that: In step II, the catalyst is any one of benzyltriethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.
5. The method for preparing a wear-resistant and highly elastic foam according to claim 1, characterized in that: The preparation method of the inorganic modified filler comprises the following steps: Add glass flakes and xylene solution into a reaction kettle, perform ultrasound to form a uniform dispersion, pass nitrogen, expel the air, then add diisocyanate monomer and tin catalyst into the dispersion, after the addition is completed, turn on the heating until the temperature in the reaction kettle reaches 85-95°C, keep stirring for 3-5 hours, then add N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, lower the system temperature to 60-70°C, stir under this temperature condition for 3-7 hours, filter and separate the solid material, wash the solid material, and vacuum dry to obtain modified glass flakes.
6. The method for preparing a wear-resistant and highly elastic foam according to claim 5, characterized in that: The diisocyanate monomer is any one of toluene-2,4-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate or diphenylmethane-4,4'-diisocyanate.
7. The method for preparing a wear-resistant and highly elastic foam according to claim 5, characterized in that: The tin catalyst is any one of stannous octoate, dibutyltin didodecylsulfide or dibutyltin dilaurate.
8. The method for preparing a wear-resistant and highly elastic foam according to claim 1, characterized in that: The foaming agent is any one of azodicarbonamide, p-toluenesulfonyl hydrazide or N,N-dinitrosopentamethylenetetramine.
9. The method for preparing a wear-resistant and highly elastic foam according to claim 1, characterized in that: In step (2), the radiation dose of the radiation cross-linking is 70 to 100 kGy.
10. A wear-resistant and highly elastic foam, characterized in that: The method is as claimed in claim 1.
Citation Information
Patent Citations
Flame-retardant foamed polyethylene material and preparation method thereof
CN102174223B